The Influence of Heat Treatment Time and Temperature on the Physical Properties of Assab-Corax Steel - A.K. Jahja; Parikin Parikin; N. Effendi (PPIKSN-BATAN, 2005)
X-ray diffraction experiment was carried out on commercial Assab-Corax steel sample. The polished samples are then heated to various temperature for different holding time; 200 oC for 4 hours, 300 oC for 4 hours, 400oC for 6-, 8-, 12- and 16 hours, 500 oC for 4 hours and 600 oC for 4 hours. The refinement of the diffraction intensity was carried out using the Im3m model, and the results show that the Carbon atoms are distributed among the base position in the body centered cubic unit cell at the eight-fold octahedral interstitial sites. Using the refined structural parameters, thermo-physical properties such as Debye temperature and coefficient of thermal expansion are calculated. From the results of the analysis it could be concluded that Debye temperature in Assab-Corrax steels tend to decrease with increasing heat-treatment time but tend to increase with heat treatment temperature. The coefficients of linear expansion also tend to decrease with increasing heat-treatment time and tend to increase with heat treatment temperature. Although the patterns are different, for example when the Debye temperature reaches its peak value for heat treatment time of 8 hours, the coefficient of linear expansion would reach its low point at this time. Therefore, the general finding is that both treatment-temperature and – time are influential to the physical properties of Assab-Corrax steels and x-ray diffraction methods could be utilized in elucidating these important findings.